2004
DOI: 10.2337/diabetes.53.8.2132
|View full text |Cite
|
Sign up to set email alerts
|

Adiponectin Receptor 1 Gene (ADIPOR1) as a Candidate for Type 2 Diabetes and Insulin Resistance

Abstract: Considerable data support adiponectin as an important adipose-derived insulin sensitizer that enhances fatty acid oxidation and alters hepatic gluconeogenesis. Adiponectin acts by way of two receptors, ADIPOR1 and ADIPOR2. ADIPOR1 is widely expressed in tissues, including muscle, liver, and pancreas, and binds the globular form of adiponectin with high affinity. To test the hypothesis that sequence variations in or near the ADIPOR1 gene contribute to the risk of developing type 2 diabetes and the metabolic syn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
55
2
1

Year Published

2005
2005
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 95 publications
(64 citation statements)
references
References 24 publications
6
55
2
1
Order By: Relevance
“…However, it cannot be excluded that SNPs in ADIPOR1 and/or ADIPOR2 had a minor effect on susceptibility to type 2 diabetes. Consistent with our results for ADPOR1, an American study recently reported that SNPs in ADIPOR1 were not associated with type 2 diabetes in Caucasians or African Americans [20]. However, they reported that the level of expression of ADIPOR1 in lymphocytes from type 2 diabetic subjects was reduced compared with that in lymphocytes from non-diabetic subjects, implicating ADIPOR1 in the pathogenesis of type 2 diabetes.…”
Section: Discussionsupporting
confidence: 91%
“…However, it cannot be excluded that SNPs in ADIPOR1 and/or ADIPOR2 had a minor effect on susceptibility to type 2 diabetes. Consistent with our results for ADPOR1, an American study recently reported that SNPs in ADIPOR1 were not associated with type 2 diabetes in Caucasians or African Americans [20]. However, they reported that the level of expression of ADIPOR1 in lymphocytes from type 2 diabetic subjects was reduced compared with that in lymphocytes from non-diabetic subjects, implicating ADIPOR1 in the pathogenesis of type 2 diabetes.…”
Section: Discussionsupporting
confidence: 91%
“…Our findings that haplotypes possessing the tagging SNPs of the ADIPOR1 gene were associated with diabetes risk lend further credibility for the potential roles of the variability of the ADIPOR1 gene in the etiology of the disease. Earlier evidence indicates that the 3Ј UTR polymorphism rs1139646 may affect the expression of the ADIPOR1 gene (15). Although rs1139646 showed the strongest and nominally significantly association with diabetes risk in the present study, it is less likely to be a polymorphic changes (in the order of rs2232853, rs10494839, rs12733285, rs1342387, rs1139646, and rs10920531) separating one haplotype from the other.…”
Section: Discussioncontrasting
confidence: 68%
“…We did not find significant associations between the variations in this gene, individually or in haplotypes, with diabetes risk in U.S. women. We have genotyped several previously reported polymorphisms including rs11061971, rs1044471, rs1342387 (14), and rs1139646 (15). Some other reported polymorphisms, rs767870, rs2286380 (tagged by rs7316374) (17), rs12342 (tagged by rs11061937), and rs2275737 (tagged by rs1342387) (14), could be well captured by the tagging SNPs used in our study (with r 2 Ͼ 0.8).…”
Section: Discussionmentioning
confidence: 54%
“…1a). Among them, three SNPs were already reported in the dbSNP database (http://ncbi.nlm.nih.gov/projects/SNP, last accessed in August 2005) and one SNP (9512 G/A) was recently found by Wang and colleagues [24] (Table 1). Pairwise linkage disequilibrium for the SNPs is shown in Table 2.…”
Section: Screening For Polymorphisms and Genotyping Resultsmentioning
confidence: 99%
“…Most recently, the group of Elbein found that SNPs in ADIPOR1 were not associated with type 2 diabetes [24]. Nevertheless, two alleles in the 3′ untranslated region were expressed unequally and mRNA of ADIPOR1 were lower among transformed lymphocytes from diabetic AfricanAmerican individuals compared with healthy controls.…”
Section: Discussionmentioning
confidence: 99%